PENGARUH PENDIDIKAN KARAKTER TERHADAP SIKAP BELAJAR SISWA UPT SPF SD INPRES MANGGALA KOTA MAKASSAR - Ratnasari; Waddi Fatimah; Baharuddin Hafid; Eka Fitriana HS (LPPM Universitas Cipta Mandiri, 2024)
This research aims to determine the effect of character education on the learning attitudes of UPT SPF SD Inpres Manggala students. This type of research is ex post facto. The sample in this study was 37 students in grades IV and V of SD Inpres Manggala, using a simple random sampling technique. The instruments used are questionnaires and documentation. Data were analyzed using descriptive and inferential statistics. Based on descriptive analysis, it shows that the average value of character education is 66.27 in the influential category and the average value of learning attitudes is 27.81 in the good category. Inferential statistical analysis shows that the normality test results for character education are 0.555 and learning attitudes are 0.182 > 0.05 (homogeneous), the linear test results for character education are 0.873 > 0.05, thus there is a linear relationship between character education and students' learning attitudes. The results of the hypothesis test show a sig value of 0.001, with the criteria of sig (0.001) <(0.05). The conclusion in this research is that there is an influence of character education on the learning attitudes of UPT SPF SD Inpres Manggala students.